PEMANFAATAN LIMBAH CUCIAN SEBAGAI SUMBER FOSFAT RAMAH LINGKUNGAN TERHADAP PERTUMBUHAN TANAMAN - Rahmat Dwi Aprian; Fadarina; Indah Purnamasari (KINETIKA, 2021)
The use of detergent in washing activities is increasing in line with the population growth rate every year. Laundry waste generated by the use of detergents contains active ingredients which are harmful to the health of living things and can damage the environment and cause eutrophication. One method of processing that can be used to treat laundry waste is by using activated carbon as an adsorbent. This study aims to determine the best conditions for treating laundry waste using activated carbon and to be able to utilize laundry waste as a source of phosphate for plant growth. Laundry waste is treated with the addition of activated carbon as much as 5, 10, 15 and 20 grams per one liter of laundry waste with a variation of time 20, 40 and 60 minutes and a constant stirring speed at 200 rpm. The parameters analyzed were pH, COD, BOD, phosphate concentration and the effect on the growth of chili plants observed for 9 weeks. The results showed that the pH level remained constant at a value of 7, and the BOD, COD and phosphate concentrations decreased to 53.6, 227.3 and 0.178 mg/L, respectively. The adsorption isotherm model is closer to the Freundlich isotherm model with R2 value of 0.9835-0.9998. And there is no significant effect on the provision of laundry waste after treatment on the growth of the tested plants.